Peningkatan Proses Pembelajaran Tematik Terpadu Dengan Menggunakan Model Problem Based Learning (PBL) di Kelas V SDN 10 Sintoga - Nuris, M Wahid; Zuardi, Zuardi (Universitas Negeri Padang, 2021)
This study aims to describe the use of the Problem Based Learning model to improve the integrated thematic learning process in the fifth grade of SD N 05 Bandar Buat Padang. This research is a classroom action research (CAR) that uses a qualitative and quantitative approach. Conducted in two cycles, with three meetings covering four stages, namely planning, implementation, observation, and reflection. The subjects of this study were researchers, teachers, and fifth grade students of SDN 10 Sintoga, totaling 27 people. The results of the study were: (1) the percentage of lesson plan observation was 79,16%, an increase of 100%. (2) Teacher activities 82,5%, an increase of 100%. (3) Student activities 82,5%, an increase of 100%.